EPEN-27. PERIOPERATIVE OUTCOMES IN PEDIATRIC EPENDYMOMAS – A RETROSPECTIVE ANALYSIS OF 47 PATIENTS. Issue 2 (22nd June 2018) - Singh, Vikas; Kattepur, Abhay; Patil, Aditya; Shetty, Prakash; Gupta, Tejpal; Chinnaswamy, Girish; Epari, Sridhar; Jalali, Rakesh; Moiyadi, Ali Asgar
Abstract: AIM: To analyze clinico-dermographic profiles and outcome in pediatric population diagnosed with ependymoma. MATERIALS AND METHODS: Pediatric (<18years) patients diagnosed with ependymoma from January 2010 to December 2015 were retrospectively analyzed. All charts, files and electronic medical records of these patients were studied. The demographic, surgical, pathological and follow up data (atleast 2 years) of these patients were collected and analyzed using SPSS version 20 software. RESULTS: During the study period, 47 pediatric patients were diagnosed with ependymoma. Mean age at diagnosis was 7.7 years with male: female ratio of 1.2: 1. Raised intracranial tension was most common presentation seen in 55.31% (n=26). 65.96% (n=31) had received some form of prior treatment (Surgery/Radiotherapy/Chemotherapy). Supratentorial location was seen in 51% (n=24). Gross total resection was achieved in 63.83% (n=30). Anaplastic ependymoma was most common histologic subtype seen in 76.6% (n=36). Post operatively adjuvant treatment (radiotherapy +/- chemotherapy) was administered to 72.34 %(n= 34). During follow up, 46.81% (n=22) patients were alive without disease while 25.53% (n=12) succumbed to the disease. In the alive without disease group, 86.36% (n=19) had undergone gross total resection. A subset analysis between grade III and grade II ependymoma showed statistical significant difference for pre-operative neurological deficits (p=0.04) and incidence of surgical site infections. (p=0.03) while there was no difference in peri-operative morbidity and mortality between the two groups. CONCLUSION: Surgery followed by adjuvant treatment in anaplastic ependymoma is associated with long term disease free survival.